A review of the current state of knowledge on Sciatica for family physicians. Diagnosis and potential treatments - Gołębski , Maciej; Nowak, Wojciech; Mikołajczyk , Jagoda; Kukla , Zuzanna; Mieruszyńska , Stella; Krzemińska , Paulina; Sawicki , Mirosław; Sadowska , Izabela; Włosiański , Jakub; Musialik , Sebastian (Quality in Sport, 2025)
Sciatica or lower back pain (LBP) with sciatic radiation is one of the most common problems in primary care. Patients with such ailment vary in age and general condition of health, with average age of patient reporting such symptoms successively lowering. The aim of this article is to broaden the knowledge of medical practitioners on diagnosis, management and potential treatments of lower back pain with sciatic radiation by reviewing available information on various aspects of diagnosing, managing and means of treatment od sciatica. Updated information on diagnosing and treating sciatica may prove crucial for family physicians or general practitioners (GP) due to ever increasing number of patients.